Compensatory award for unfair dismissal in Malaysia: Criterions in assessment of award - Shair Mohamed, Mohd Akram; Ali Mohamed, Ashgar Ali; Sardar Baig, Farheen Baig (International Organization Center of Academic Research (OCERINT), 2016)
Dismissal from employment is the prerogative of the employer emanating from various reasons such as unsatisfactory or poor work performance, incompetency, absenteeism, insubordination, stealing, assault, bullying, drunkenness, serious violation of employer's policies and practices, damaging employer’s property and using employer’s property for personal business, among others. The burden is on the employer to prove that the dismissed was justified. Where a dismissal was adjudged to be without just cause or excuse, the Industrial Court will award appropriate remedy and this include compensatory award. The Industrial Relations Act 1967 (IRA) merely mentioned reinstatement as the sole remedy for dismissal without just cause or excuse. The power of the Industrial Court to award monetary compensation was resolved by the former Federal Court in Assunta Hospital v Dr A Dutt [1981] 1 MLJ 105, where the Court held inter alia, that where reinstatement would not be an appropriate remedy, the Industrial Court has the power to award monetary compensation based on the provisions of section 30(4), (5) and (6) of the IRA. Although the Act did not specify the types and criterions for its assessment, nevertheless the monetary award in favour of the unfairly dismissed worker must be fair and adequate to compensate him for the loss of employment. In practice however, the assessment or measure of the monetary award is at the discretion of the Industrial Court based on the particular facts, circumstances and substantial merits of the case, and assessed in accordance with equity and good conscience under section 30(5) of the IRA. The amount however, should not be excessive to the extent of financially burdening the employer. In light of the above, this paper discusses the compensatory awards of the Industrial Court in successful unfair dismissal claims with a view of highlighting the criterions used in its assessment.